Date Seeds Flour Used as Value-Added Ingredient for Wheat Sourdough Bread: An Example of Sustainable Bio-Recycling - Ameur, Hana; Cantatore, Vincenzo; Filannino, Pasquale; Cavoski, Ivana; Nikoloudaki, Olga; Gobbetti, Marco; Di Cagno, Raffaella (Frontiers in Microbiology, 2022)
Our study proposed date seeds flour (DSF) as an innovative ingredient for sourdough bread production through a sustainable bio-recycling. We isolated autochthonous lactic acid bacteria and yeasts from DSF and DSF-derived doughs, to build up a reservoir of strains from which to select starters ensuring rapid adaptation and high ecological fitness. The screening based on pro-technological criteria led to the formulation of a mixed starter consisting of Leuconostoc mesenteroides, Lactiplantibacillus plantarum and Saccharomyces cerevisiae strains, which allowed obtaining a mature type I sourdough after consecutive refreshments, in which an aliquot of the durum wheat flour (DWF) was replaced by DSF. Resulting DSF sourdough and bread underwent to an integrated characterization. Sourdough biotechnology was confirmed as suitable procedure to improve some functional and sensory properties of DWF/DSF mixture formulation. Radical scavenging activity resulted increased due to the consistent release of free phenolics. Perceived bitterness and astringency were considerably diminished, likely because of tannin degradation.